2002
DOI: 10.1021/ja027371v
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Isomerism in Coordination Compounds:  Nanoscale Molecular Hexagons and Chains

Abstract: A nanoscale supramolecular hexagon, 1, and its supramolecular isomeric chain structure, 2, have been prepared from self-assembly of 5-NO2-bdc and Cu(II) cations. The hexagon is neutral and soluble and has outer and inner diameters of 3.1 and 0.8 nm, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
122
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(125 citation statements)
references
References 26 publications
3
122
0
Order By: Relevance
“…The sip ligands reported here coordinate to metal atoms in different coordination modes, namely as d-sip in MCCP-4 and e-sip in MCCP-5, respectively. With regards to the nip ligand, the only other metal-(nip) complexes which have been prepared are two Cu(nip) supramolecular isomers [11] and two Zn(nip) supramolecular structures, namely {[Zn(nip)(py)(…”
Section: Introductionmentioning
confidence: 99%
“…The sip ligands reported here coordinate to metal atoms in different coordination modes, namely as d-sip in MCCP-4 and e-sip in MCCP-5, respectively. With regards to the nip ligand, the only other metal-(nip) complexes which have been prepared are two Cu(nip) supramolecular isomers [11] and two Zn(nip) supramolecular structures, namely {[Zn(nip)(py)(…”
Section: Introductionmentioning
confidence: 99%
“…We are aware of only one case in which a reaction has yielded both a discrete complex and an extended polymeric structure from the same building block. [7] However, we know of no examples in which these two general topologies were found to co-exist in a stable crystalline solid. Herein, we report the synthesis of a self-assembling, self-complementary metal complex that forms a supramolecular hexagon and a double-helical coordination polymer within a single crystalline lattice.…”
mentioning
confidence: 99%
“…3) and c g ···c g distance (Janiak, 2000) is 4.17 Å. The similar supramolecular synthons R 2 2 (10) and R 2 2 (12) (Bernstein et al, 1995) have been also observed in crystal structure of one dinuclear complex (Valigura et al, 2006) and several polymeric complexes (Abourahma et al, 2002;Burrows et al, 2008;Cao et al, 2008;Korabik et al, 2011;Maharramov et al, 2012;Vaskova et al, 2011;Xu et al, 2007;Yamada et al, 1998). The crystal packing of 1 is shown in Fig.…”
Section: Resultsmentioning
confidence: 70%